2008
DOI: 10.1186/1471-2458-8-164
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal relationship between job mobility, perceived organizational justice, and health

Abstract: Background: The main purpose of the present study was to examine the 2-year longitudinal and reciprocal relationship between job mobility and health and burnout. A second aim was to elucidate the effects of perceived organizational justice and turnover intentions on the relationship between job mobility (non-, internally and externally mobile), and health (SF-36) and burnout (CBI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 35 publications
6
25
1
1
Order By: Relevance
“…As such, organizational justice offers multiple target areas for interventions (e.g., leaders awareness or addressing organizational culture and processes [35,36]), especially if longitudinal studies confirm our observations. The observation that the association of organizational justice with tinnitus was mediated through burnout and depressive symptoms is in line with our hypothesis based on recent evidence showing organizational justice to affect burnout [13,19,37,38] and depression [13][14][15][16][17][18], which in turn have been found to be associated with tinnitus [25]. The present study additionally revealed that mediation occurred especially through burnout and to a lesser extent through depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As such, organizational justice offers multiple target areas for interventions (e.g., leaders awareness or addressing organizational culture and processes [35,36]), especially if longitudinal studies confirm our observations. The observation that the association of organizational justice with tinnitus was mediated through burnout and depressive symptoms is in line with our hypothesis based on recent evidence showing organizational justice to affect burnout [13,19,37,38] and depression [13][14][15][16][17][18], which in turn have been found to be associated with tinnitus [25]. The present study additionally revealed that mediation occurred especially through burnout and to a lesser extent through depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Distributive justice refers to the fair allocation of outcomes, while procedural justice characterizes the fairness of the decision-making process [10,11], and interactional justice describes the fairness of interpersonal interactions with superiors [12]. Prospective studies documented that organizational justice predicts depression [13][14][15][16][17][18] and emotional exhaustion/ burnout [13,[19][20][21], which have all been associated with tinnitus [4,[22][23][24][25]. However, the association of organizational justice with tinnitus has hitherto not been tested.…”
Section: Introductionmentioning
confidence: 99%
“…This made it impossible to determine external turnover (i.e. change of workplace outside the organization or retirement) (Liljegren & Ekberg 2008). The outcome variable of internal turnover (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…2007) and we found none addressing the actual turnover of health‐care managers. Some distinctions have been made between internal (change of position within the organization) and external (change of workplace outside the organization or retirement) turnover (Liljegren & Ekberg 2008). The impact on the direct financial costs of recruitment and the indirect costs caused by loss of competence and productivity have been highlighted (Mor Barak et al.…”
Section: Introductionmentioning
confidence: 99%
“…Existe un amplio consenso sobre la relación existente entre el entorno psicosocial del trabajo y el burnout [7][8][9] , incluyendo conceptos como la justicia, la equidad o la reciprocidad 10 , así como entre el burnout y distintos efectos sobre las personas 11,12 , sobre las organizaciones 13 o sobre la sociedad 14,15 . Se observan diferencias entre distintas ocupaciones y entornos 16,17 .…”
Section: Introductionunclassified